From "quick fix" to lasting commitment: Using root cause analysis to address disproportionate discipline outcomes. Issue 1 (2nd January 2022) - Sandomierski, Therese; Martinez, Stephanie; Webster, Rebecca; Winneker, Anna; Minch, Devon
ABSTRACT: Root Cause Analysis (RCA) has been recommended as a specific problem-solving approach for addressing disproportionate discipline outcomes. RCA differs from other problem-solving models through its in-depth analysis that draws from the perspectives of individuals who are impacted by the issue being addressed. When applied to disproportionate discipline, this means that RCA would include perspectives from all school staff, as well as students and families who are over-represented in discipline outcomes. This paper describes an approach to conducting RCA and presents two case studies that illustrate what stakeholders may gain by incorporating RCA into a school's efforts to increase disciplinary equity. Suggestions for first steps school teams can take to conduct a root cause analysis will be provided.